RANCANGAN TATA KELOLA PEREMAJAAN RUANG KELAS DIREKTORAT PEMBINAAN SEKOLAH DASAR - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2016)
Rejuvenation classroom is a reference to the Directorate of Primary School activity conducted on an ongoing basis. So the availability, truth and certainty of information from the renovation must show current conditions in order to meet the needs of the coaching process, accountability and financial audit, as well as in the management of data rejuvenation should be integrated in one unified database. Then it is necessary to build an application that is able to manage the process of rejuvenation consistently. In the design of the governance renewal application classrooms, use agile software development methodology with extreme approach to programming process to explain each activity in each phase of the design. Stages of design and implementation is limited to the aid management process module rejuvenation classroom consisting of the proposed input, input the data verification process, the process of filing the disbursement of funds, the process of managing the data returns, and the handling of school accountability reports. With the construction of this rejuvenation governance can help meet the needs of data and information quickly and accurately. So that the information presented can be used as one of the considerations in the process of planning, policy making, monitoring, evaluation and inspection.